Penggunaan Media POM Terhadap Kemampuan Pemahaman Matematis Siswa SMK Pada Materi Matriks - Setiyani; Trusti Hapsari; Laela Sagita (Universitas PGRI Adi Buana Surabaya, 2021)
The learning process that has taken place so far is still teacher-centered, dominated by high-achieving students, and the learning atmosphere is not conducive. The use of Learning Media Matrix Operation Board (POM) is expected to direct attention and stimulate students' minds to respond to a lesson. This study aims to determine student responses to the use of POM Learning Media, increase the ability to understand mathematical concepts using the Matrix Operation Board Learning Media, classical completeness and individual completeness of students using POM Media. The method used in this research is the experimental method. The research was conducted at SMK Negeri 1 Lemahabang with purposive sampling technique, namely class X TKJ 1. The results showed that the student's response to learning using a matrix operation board was 83.76%, so the response rate was very strong. there is an increase in the ability to understand mathematical concepts using POM media, the average increase reaches 0.64 with moderate interpretation. Individual completeness can be seen from the average acquisition of individual students, which is 72.2, while the classical completeness of the percentage of students is 80% complete in learning the matrix operation material. POM media can improve students' ability to understand mathematical concepts.